The impact of competition on elephant musth strategies: a game–theoretic model - Wyse, John Max; Hardy, Ian C.W.; Yon, Lisa; Mesterton-Gibbons, Mike (Elsevier, 2017)
Mature male African Savannah elephants are known to periodically enter a temporary state of heightened aggression called “musth,” often linked with increased androgens, particularly testosterone. Sexually mature males are capable of entering musth at any time of year, and will often travel long distances to find estrous females. When two musth bulls or two non-musth bulls encounter one another, the agonistic interaction is usually won by the larger male. However, When a smaller musth bull encounters a larger non-musth bull, the smaller musth male can win. The relative mating success of musth males is due partly to this fighting advantage, and partly to estrous females’ general preference for musth males.